Oil price movements and exchange rate: evidence from selected net oil exporting countries in Africa - Mdluli, Thobeka (Graduate School of Business (GSB), 2022)
This dissertation investigates the long and the short run relationships as well as the causal relationship between oil price movements and exchange rates. The study uses daily data for a 12-year period commencing in January 2007 and December 2018, focuses on four net oil exporting African countries, namely, Nigeria, Angola, Algeria and Egypt. The data was analysed using the time series techniques covering unit root, cointegration and causality analyses. The results of the study found that in the long run, oil prices movements are observed to be negatively related to the returns on the Nigerian Naira, Egyptian Pounds and Algerian Dinar indicating that an oil price increases result in the depreciation of the exchange rates for each of the aforementioned countries. In the short run, oil prices movements are observed to be positively related to the returns on Nigerian Naira, Egyptian Pounds and Algerian Dinar indicating that oil price increase results in the appreciation of the exchange rates. The causality results show evidence of bidirectional causality for the Nigerian Naira and the Angolan Dinar, unidirectional causality for the Egyptian pound and lastly no evidence of causality was found for the Angolan Kwanza. This dissertation suggests the policymakers to stabilize the effects of oil price movements through expansionary monetary policy, to shield African economies from sudden economic depression.